Notch signaling at a glance - Hori, Kazuya (The Company of Biologists, 2013)
Cell–cell interactions define a quintessential aspect of multicellular development. Metazoan morphogenesis depends on a handful of fundamental, conserved cellular interaction mechanisms, one of which is defined by the Notch signaling pathway. Signals transmitted through the Notch surface receptor have a unique developmental role: Notch signaling links the fate of one cell with that of a cellular neighbor through physical interactions between the Notch receptor and the membrane-bound ligands that are expressed in an apposing cell. The developmental outcome of Notch signals is strictly dependent on the cellular context and can influence differentiation, proliferation and apoptotic cell fates. The Notch pathway is conserved across species (Artavanis-Tsakonas et al., 1999; Bray, 2006; Kopan and Ilagan, 2009). In humans, Notch malfunction has been associated with a diverse range of diseases linked to changes in cell fate and cell proliferation including cancer (Louvi and Artavanis-Tsakonas, 2012). In this Cell Science at a Glance article and the accompanying poster we summarize the molecular biology of Notch signaling, its role in development and its relevance to disease.